Abordagem de conceitos sobre eletrostática no ensino médio através de uma oficina de ensino de Física - Silva, Carlos Augusto (2019)
A Physics workshop is a hands-on activity that can be used in the classroom or in the counter-time to increase student motivation in introductory physics courses at any level. In addition to helping students acquire a good conceptual foundation, it can contribute significantly to applying this knowledge in problem solving and engaging students in scientific practice. In this work we propose the elaboration of a workshop for the teaching of electrostatics. Our purpose was to show that experimentation in an investigative context in the format of a workshop can contribute significantly to facilitate the understanding of several abstract concepts such as electric charge, electric current, electric field and electric potential. This proposal was applied to three schools in the outback of the state of São Paulo for approximately 60 students. During the construction of the experiments the students used the logbook method to write down their observations, make hypotheses and answer questionnaires. With this procedure the student had the opportunity to participate in their own learning, exploring the advantages of scientific activity through investigative experimental proposals. The use of the workshop can be an interesting alternative to minimize the usual reductionism caused by the handout method, which is increasingly present in schools, to improve the relationship between teacher and students and to serve as a complementary methodology to theoretical physics classes. Our proposal was very well received in the classroom, having a motivating and integrative character for the teaching of electrostatic contents. Our educational product consists in the elaboration of a methodology for the application of a kit composed of a Kelvin electrostatic water dropper generator and other common experiments for the detection of electric fields, such as the electric pendulum, the electroscope, and also a handbook written in a simple and appropriate language for the high school physics teacher containing all the details of the construction and application of the kit.